2012
DOI: 10.1371/journal.pone.0029473
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Plant Identification Using Species- and Group-Specific Primers Targeting Chloroplast DNA

Abstract: Plant identification is challenging when no morphologically assignable parts are available. There is a lack of broadly applicable methods for identifying plants in this situation, for example when roots grow in mixture and for decayed or semi-digested plant material. These difficulties have also impeded the progress made in ecological disciplines such as soil- and trophic ecology. Here, a PCR-based approach is presented which allows identifying a variety of plant taxa commonly occurring in Central European agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…Where most molecular studies target single predators or a few species only, a small but growing number of studies have developed molecular tools to resolve smaller and larger modules within food webs, from plant-herbivore interactions (Staudacher et al 2011;Wallinger et al 2012;Garcia-Robledo et al 2013a, 2013bKitson et al 2013;Kajtoch et al 2015) to plant -leaf minerparasitoid networks (Derocles et al 2015). The food webs of soils offer a particular challenge-and particular scope for new insights-as species diversity is relatively high, trophic relations complex, and direct feeding interactions oftentimes impossible to observe.…”
Section: Reconstructing Larger Modules Within Terrestrial Websmentioning
confidence: 99%
“…Where most molecular studies target single predators or a few species only, a small but growing number of studies have developed molecular tools to resolve smaller and larger modules within food webs, from plant-herbivore interactions (Staudacher et al 2011;Wallinger et al 2012;Garcia-Robledo et al 2013a, 2013bKitson et al 2013;Kajtoch et al 2015) to plant -leaf minerparasitoid networks (Derocles et al 2015). The food webs of soils offer a particular challenge-and particular scope for new insights-as species diversity is relatively high, trophic relations complex, and direct feeding interactions oftentimes impossible to observe.…”
Section: Reconstructing Larger Modules Within Terrestrial Websmentioning
confidence: 99%
“…All wireworm/regurgitate samples were screened for plant DNA applying multiplex PCR assays described in Wallinger et al (2012). Each sample was tested with a duplex PCR to detect DNA of wheat and maize (duplex ''TZ''), while samples stemming from the MIX treatment were additionally tested with another duplex PCR for lupine and buckwheat (duplex ''LF'') and a multiplex PCR to detect DNA fragments of buckwheat, ryegrass, beans, and mustard (multiplex ''FLPS'').…”
Section: Consumption Of Maize and Associated Plantsmentioning
confidence: 99%
“…Wallinger et al (2012) also revealed that an overall reliable sequence alignment of all studied species, including grasses, was impossible due to the great length differences in noncoding regions even within closely related taxa. Should the SNP markers developed here prove to be species-specific, they would provide a valuable tool for reliable diagnosis of grasses.…”
Section: Discussionmentioning
confidence: 99%